Elevated Gestational IL-13 During Fetal Development Is Associated With Hyperactivity and Inattention in Eight-Year-Old Children - Thürmann, Loreen; Herberth, Gunda; Rolle-Kampczyk, Ulrike; Röder, Stefan; Borte, Michael; von Bergen, Martin; Lehmann, Irina; Trump, Saskia (Frontiers in Immunology, 2019)
Maternal immune activation during fetal development leads to behavioral and psychological disorders in the offspring. Concomitantly, insufficient supply of polyunsaturated fatty acids (PUFAs) is suspected to contribute to early neuronal maldevelopment due to the immune modulatory capabilities of PUFAs. However, human data are missing considering both of these aspects and their impact on children’s behavioral outcomes. In line, this study aimed to elucidate the influence of gestational cytokines and PUFA-containing lipids during late pregnancy on behavioral sequelae in childhood, particularly focusing on an immune activation shaped by a history of maternal atopic diseases instead of a pathogen-mediated immune response. Based on the prospective mother-child cohort LINA we assessed the unstimulated blood plasma cytokine profiles and concentrations of PUFA-containing lipids of 293 mothers at the 34th week of pregnancy. Maternal history of atopic diseases was obtained from questionnaires and behavior in eight-year-old children was assessed by the standardized Strength and Difficulties Questionnaires generating scores for hyperactivity/inattention, emotional symptoms, conduct problems, and peer relationship problems. Elevated IL-13 increased the risk for the child to show behavioral difficulties, in particular, hyperactive/inattentive behavior (adj.OR (95% CI): 2.47 (1.51-4.02), n=255 vs. 38) at the age of eight years. Although the presence of maternal atopic dermatitis (AD) was associated with increased gestational IL-13 concentrations (adj.MR (95% CI): 1.17 (1.04-1.32)), no effect on children’s behavioral difficulties was observed. However, a decrease in the PUFA containing lipid species PC aa C38:6 was not only associated with an increased gestational IL 13 concentration but also mediates the indirect effect of low PC aa C38:6 concentrations on children’s abnormal behavior independent of maternal AD. We additionally assessed whether maternal IL-13 and PC aa C38:6 concentrations translate their effect by altering children’s cord blood PC aa C38:6 and IL-13. While also the children’s cord blood IL-13 was related to children’s behavior, no effect of children’s PC aa C38:6 was observed. This is the first study demonstrating that elevated gestational IL-13increases the risk for children to develop behavioral difficulties. Analyses suggest that a reduced supply of gestational PC aa C38:6 contributes to elevated gestational IL-13 leading to behavioral sequelae in the offspring.